SATB2-associated syndrome: a case report - Issad Mehdi; Ahossi Victorin; Melli Emma; Hoarau David (Journal of Oral Medicine and Oral Surgery, 2024)
Introduction: SATB2-associated syndrome is an extremely rare genetic disorder. It is characterized by delayed neurocognitive development, craniofacial anomalies and dental defects. Observation: This case report highlights the craniofacial and dental phenotype linked to a mutation resulting in SATB2-associated syndrome affecting a 13-year-old boy. Conclusion: The diagnosis of this syndrome is very difficult. The management using a multidisciplinary strategy includes among others, oral hygiene maintenance, orthodontic treatment and intensive speech therapy.